Handmade paper : from rags to riches - Dass, Laxmi; Akhil Bhartiya Gramodhyog Mahasangh (New Delhi : Akhil Bhartiya Gramodhyog Mahasangh and Concept, 2009)
Contributed articles tracing the history and development of handmade paper in India.
Includes bibliographical references and index.
Keywords: Paper, Handmade -- India -- History; Papermaking -- India -- History; Paper industry -- Technological innovations -- India